Pengembangan Aplikasi Mobile Portal Akademik (MyCIC) dengan Pendekatan FAST untuk Peningkatan Layanan Akademik (Studi Kasus : Universitas Catur Insan Cendekia) - Sahl; Petrus Sokibi; Rifqi Fahrudin (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2025)
The MyCIC web-based academic portal at Universitas Catur Insan Cendekia (UCIC) faces accessibility and user experience challenges on mobile devices. The unresponsive and passive system creates information gaps due to the absence of proactive notifications, hindering the effectiveness of academic services. This research aims to design and build a native mobile application to improve the ease of access and quality of academic communication. The system development applied the Framework for the Application of System Thinking (FAST) method, focusing on UI/UX principles using Kotlin and Android Studio. The resulting application was then validated through two stages of testing. First, black-box testing shows that all functionality runs as designed without critical errors. Second, usability testing involving 20 respondents using the System Usability Scale (SUS) questionnaire resulted in a final score of 80.88, which falls into the “Excellent” category. This combination of test results proves that the developed MyCIC application is not only technically successful, but also very well received by users as an effective solution to improve academic services in the UCIC environment.